2-Methylbenzimidazolium thiocyanate - Shaker, S.A.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
In the crystal structure of the title compound, C8H9N2+center dot SCN-, the nearly planar 2-methylbenzimidazolium cation [r.m.s. deviation = 0.0123 (4) angstrom] is perpendicular to a mirror plane and the methyl H atoms are disordered about the mirror plane with equal occupancies. The thiocyanate anion also lies on a mirror plane. N-H center dot center dot center dot N hydrogen bonds link the components into an infinite chain along the b axis.